2021
DOI: 10.1002/app.50598
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dehydrochlorination of pure PVC polymer: Part I—thermal degradation kinetics by thermogravimetric analysis

Abstract: Thermal degradation of PVC occurs in two stages, with each stage subdivided into two substages. The first refers to the dehydrochlorination, where hydrochloric acid is formed, and giving polyene structures. Hitherto, the degradation mechanism and action of hydrochloric acid as a catalyst during the dehydrochlorination stage are poorly known. Recently, the importance of the tacticity has gained attention for its influence on the dehydrochlorination mechanism. The present work focused on the dehydrochlorination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 67 publications
(251 reference statements)
4
24
0
Order By: Relevance
“…Moreover, in Figure 8 , the activation energy for the first substage of the dehydrochlorination of PVC/Pb and PVC/CaZn tended to decrease from 10% conversion until approximately 40% conversion and increasing thereafter as similarly reported in Ref. [ 25 ]. These characteristics confirmed that the energy required to break the C-Cl bond in the first substage of dehydrochlorination is high.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, in Figure 8 , the activation energy for the first substage of the dehydrochlorination of PVC/Pb and PVC/CaZn tended to decrease from 10% conversion until approximately 40% conversion and increasing thereafter as similarly reported in Ref. [ 25 ]. These characteristics confirmed that the energy required to break the C-Cl bond in the first substage of dehydrochlorination is high.…”
Section: Resultssupporting
confidence: 81%
“…The first stage is mainly attributed to dehydrochlorination by the removal of hydrogen chloride from the PVC main chain, thus forming a conjugated polyene structure. The second stage is mainly attributed to the fracture of conjugated polyene structures to form small molecular weight linear or cyclic hydrocarbons, and finally tar formation [ 25 , 26 ]. In addition, it was observed that there is a substage in the first stage of the PVC, indicating the existence of different events in this stage, suggesting a complex dehydrochlorination mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated by the viscosimetric analysis and its response to the temperature and heat flow using thermogravimetric analysis (TGA). Polymeric solutions are generally non-Newtonian fluids, but they possess intrinsic properties and thereby possess the ability to increase the viscosity of the composites [20]. Due to its easy processability, PMMA is a good viscosifier and provides good polymer-additive interaction [21].…”
Section: Characterizationmentioning
confidence: 99%
“…Due to our country's rich coal resources, acetylene hydrochlorination based on the coal route is the main process for the synthesis of vinyl chloride monomer (VCM) in China, which provides raw materials for the polyvinyl chloride (PVC) industry. [1] However, the HgCl 2 catalyst used in this process is volatile and toxic, which seriously endangers the environment and lives. In recent years, it has gradually been restricted by the scarcity of mercury resources and environmental protection policies.…”
Section: Introductionmentioning
confidence: 99%